Milliscale reactors for integration of continuous precipitation and filtration. Issue 11 (8th August 2022) - Pons Royo, Maria del Carme; Montes‐Serrano, Ignacio; Valery, Eric; Jungbauer, Alois; Satzer, Peter
Abstract: BACKGROUND: The development of integrated continuous biomanufacturing processes faces a significant challenge when the parameters for the design of the process cannot be accurately estimated from those of batch experiments. Process design is even more challenging if the outcome of one unit operation highly influences the performance of the subsequent one, such as in harvesting of a precipitate by filtration. In the case of protein precipitation, results from the batch and continuous experiements deviate and their scale‐down is limited. Microfluidics suffer from poor mixing characteristics. Thus, milliscale devices were developed to maintain mixing performance but at the expense of a slightly larger scale. RESULTS: Milliscale devices were developed for the precipitation of antibodies in continuous tubular reactors to compare different dosage times in small scale. The reactors have multiple addition points for precipitant for the continuous, controlled and precise addition of the precipitating agent without valves. The designed devices have a narrow residence time distribution to achieve fast mixing and a small volume that reduces the time and cost for experiments tenfold. Milliscale devices were used to evaluate the most appropriate dosage time for protein precipitation, thus improving purity by a factor of 3 compared to single addition. The resulting filterability of precipitates in tangential flow filtration and depth filtration was improved. CONCLUSION: Results demonstrated that multiple additions were more beneficial than single addition because they help to reduce pressure and increase filter capacity. Such devices can be used to determine and adjust the precipitation methodology to optimize floc formation and improve solid–liquid separation while reducing development time and cost. © 2022 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).